What Can Primary Care Learn From Sports Teams?. Issue 3 (July 2016) - Fiscella, Kevin; Fogarty, Colleen; Salas, Eduardo
Abstract : Teams are familiar to sports but relatively new to primary care. In this perspective, we use sports teams to illustrate key principles from team science and extract practical lessons for primary care teams. The most notable lessons include the need for continuous team learning based on presession planning and postsession debriefing, real-world team training focused on identified teamwork needs, and on-site team coaching. Implementation of these principles requires organizational commitment coupled with alignment of continuing medical education and recertification requirements with primary care teamwork competencies.